2016
DOI: 10.1149/2.1061702jes
|View full text |Cite
|
Sign up to set email alerts
|

PEM Fuel Cell Start-up/Shut-down Losses vs Temperature for Non-Graphitized and Graphitized Cathode Carbon Supports

Abstract: One of the key figures for the success of proton exchange membrane fuel cells (PEMFCs) in automotive applications is lifetime. Damage of the cathode carbon support, induced by hydrogen/air fronts moving through the anode during start-up/shut-down (SUSD), is one of the lifetime limiting factors. In this study, we examine the impact of varying the temperature at which SUSD events take place, both experimentally and by a kinetic model. For MEAs with conventional carbon supports, the model prediction of carbon oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 19 publications
7
85
1
Order By: Relevance
“…Figure 4D) from a BOL value of ≈38 μm/(mg Pt cm −2 ) (or ≈33 μm/(mg C cm −2 ), which agrees with the 28 ± 2 μm/(mg C cm −2 ) reported in literature) 36 to ≈23 μm/(mg Pt cm −2 ) and points to a collapse of the CL structure which can inhibit effective mass transport of reactants and that is supported by the drastic performance decline in the H 2 /air I/E curves in Figure 2A. The CL collapse can be attributed to carbon support corrosion in the applied potential regimes [20][21][22]37,38 and the resulting CL porosity decrease has been demonstrated by Schulenburg et al 39 in a FIB-SEM tomography study. On the other hand, representative cross section images before/after the load-cycle AST (Figures 3D/3F) do not indicate significant morphology/porosity changes concomitant with the negligible decrease in thickness to ≈34 μm/(mg Pt cm −2 ) discernable from Figure 4B.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 4D) from a BOL value of ≈38 μm/(mg Pt cm −2 ) (or ≈33 μm/(mg C cm −2 ), which agrees with the 28 ± 2 μm/(mg C cm −2 ) reported in literature) 36 to ≈23 μm/(mg Pt cm −2 ) and points to a collapse of the CL structure which can inhibit effective mass transport of reactants and that is supported by the drastic performance decline in the H 2 /air I/E curves in Figure 2A. The CL collapse can be attributed to carbon support corrosion in the applied potential regimes [20][21][22]37,38 and the resulting CL porosity decrease has been demonstrated by Schulenburg et al 39 in a FIB-SEM tomography study. On the other hand, representative cross section images before/after the load-cycle AST (Figures 3D/3F) do not indicate significant morphology/porosity changes concomitant with the negligible decrease in thickness to ≈34 μm/(mg Pt cm −2 ) discernable from Figure 4B.…”
Section: Resultssupporting
confidence: 90%
“…18 Following this recent study, in this work the durability of Pt 3 Ni aerogels in the PEFC is investigated for two different accelerated stress tests (ASTs) proposed by the DOE and compared to a commercial Pt/C benchmark. The first AST exposes the catalyst to the potential regime of 1.0 to 1.5 V RHE , which can occur in an operating PEFC during fuel starvation and start-up/shut-down of the cell and triggers C-support corrosion, 5,[19][20][21][22] and that will be referred to as 'start-stop degradation' in the following. 23 The second AST which has not been investigated in the studies cited above simulates the variation in power output present during automotive application that results in potential fluctuations between ≈0.6 and ≈1.0 V RHE causing Pt dissolution (and re-deposition); 21,[24][25][26] it will be denoted 'load-cycle degradation '.…”
mentioning
confidence: 99%
“…Step 80 600 4000 800 80 4000 800 80 4000 600 inlet pressures in the range of 12 -47 kPa gauge,inlet (no further correction for actual absolute ambient pressure was applied). At constant dry gas pressure and applied gas flow rates of 113 nccm (H 2 or air on the anode and air on the cathode), the H 2 /air anode gas front residence time was ≈ 1.3 s in all experiments (cf., Equation 20 in our previous publication), 9 and the dwell time in between gas fronts was 120 s in all cases. Note that one SUSD cycle in this work refers to the combination of one shut-down and one start-up event.…”
Section: Mea Conditioning-allmentioning
confidence: 80%
“…Hardware, set-up and materials.-For SUSD experiments, the materials and devices used were the same as in our previous publication. 9 In short, single-cell PEMFC experiments were carried out on a customized G60 test station (Greenlight Innovation Corp.) using a 50 cm 2 cell hardware with quadruple-serpentine flow-fields (Fuel Cell Technologies, Inc.). Commercial CCMs (Primea Mesga A510.1/M715.18/C580.4, W. L. Gore GmbH) with catalysts based on a high surface area carbon support and applied at loadings of 0.1/0.4 mg Pt • cm −2 (anode/cathode) were sandwiched in between two SIGRACET 25BC (SGL Carbon GmbH) gas diffusion layers (GDLs).…”
Section: Methodsmentioning
confidence: 99%
“…z E-mail: jan.schwaemmlein@tum.de gas front residence time, 16 and the degree of graphitization of the cathode catalyst support. 11,17 In contrast to the frequently investigated degradation of the cathode during a SUSD event, the anode stability over the course of SUSD cycles was only rarely examined 11,10 and generally neglected. However, Engl et al recently showed that SUSD in high temperature phosphoric acid fuel cells leads to significant amounts of carbon corrosion on the anode, along with a loss of Pt electrochemical surface area (ECSA), a finding which the authors attributed to the change of the anode potential upon switching the gas atmosphere between H 2 and air.…”
mentioning
confidence: 99%